2014
DOI: 10.1108/qmr-12-2013-0094
|View full text |Cite
|
Sign up to set email alerts
|

Brand meaning gaps and dynamics: theory, research, and practice

Abstract: Purpose – The purpose of this paper is twofold. First, propositions in an existing conceptual framework are empirically explored to note whether and how brand meaning gaps exist for internal and external stakeholders of a focal brand. Second, a typology of brand meaning gaps, characterised by meaning assonance and valence, offers new insight for brand management strategy. Design/methodology/approach – The authors use case study methods t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…Furthermore, the articles also showed that what consumers perceive and appreciate most about family firms relates to their ability to establish and maintain relational bonds with their customers (Carrigan & Buckley, 2008;Presas et al, 2014). The same meanings were also revealed in empirical studies that focused on family-based brands, where brand values such as consistency, enduring commitment, integrity, and attention to creating strong bonds with stakeholders were underlined (Krappe et al, 2011;Peters & Frehse, 2011;Wilson et al, 2014). Thus, most of the meanings attached to family firms have positive valence, and only a few studies disclosed negative consumer perceptions, such as the limited product selection and price/value in retail (Carrigan & Buckley, 2008;Orth & Green, 2009).…”
Section: The Micro Levelmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the articles also showed that what consumers perceive and appreciate most about family firms relates to their ability to establish and maintain relational bonds with their customers (Carrigan & Buckley, 2008;Presas et al, 2014). The same meanings were also revealed in empirical studies that focused on family-based brands, where brand values such as consistency, enduring commitment, integrity, and attention to creating strong bonds with stakeholders were underlined (Krappe et al, 2011;Peters & Frehse, 2011;Wilson et al, 2014). Thus, most of the meanings attached to family firms have positive valence, and only a few studies disclosed negative consumer perceptions, such as the limited product selection and price/value in retail (Carrigan & Buckley, 2008;Orth & Green, 2009).…”
Section: The Micro Levelmentioning
confidence: 82%
“…The quantitative papers generally adopted a psychological and cognitive perspective to identifying the attributes consumers attached to family-owned firms compared to non-family-owned ones (e.g., Beck & Kenning, 2015;Beck & Prügl, 2018;Binz Astrachan et al, 2013;Orth & Green, 2009;Sageder et al, 2015;Schellong, Kraiczy, Malär, & Hack, 2019). The qualitative papers were mainly interested in unveiling consumers' perceptions and the meanings relating to the relationships and face-to-face interactions between consumers and members of family businesses (see Carrigan & Buckley, 2008;Krappe et al, 2011;Lyman, 1991;Presas, Guia, & Muñoz, 2014;Wilson, Bengtsson, & Curran, 2014).…”
Section: The Micro Levelmentioning
confidence: 99%
“…Based on the results, it is concluded that people today still perceive umbrella-canopy as an icon of Braga Permai. Although not every visitor understands the history of the restaurant [19,20,21], but the where and how the umbrella-canopies are located have made them iconic.…”
Section: Conclusion and Recommendationmentioning
confidence: 99%
“…This represents a research gap in studying the combining effects of institutions and organizational capabilities, which influence opportunity identification and exploitation (Lubatkin et al, 2006;Teece, Pisano, and Shuen, 1997;Wilson et al, 2014). In our research, we aim to fill this research gap by linking firms' organizational ambidexterity, brand reputation, and brand performance and further posit a dual ambidextrous emphasis on firms' exploratory and exploitative innovation strategies through the mediating effects of brand reputation.…”
Section: Brand Ambidexteritymentioning
confidence: 99%